A Study on the Influence of Authoritarian-Benevolent Leadership on Employees' Innovative Behavior From the Perspective of Psychological Perception—Based on Fuzzy Set Qualitative Comparative Analysis - Meng, Lingxi; Li, Tong; Yang, Mengyuan; Wang, Shanshan (Frontiers in Psychology, 2022)
Employee innovation is the key to enhancing the core competitiveness of an enterprise, and leadership style plays an important role in stimulating employees' innovative behavior. This study explores the impact of unique ambidextrous leadership in the Chinese context, authoritarian-benevolent leadership, on employees' innovative behavior from the perspective of employees' psychological perception, based on research data from 430 employees of companies with direct leaders. Based on the configuration theory, using the fuzzy set qualitative comparative analysis method, the configuration analysis was carried out by taking authoritarian-benevolent ambidextrous leadership and employees' psychological perception as the influencing factors and obtained five configurations of high-level employees' innovative behavior. The results show that the combination of individualized care, understanding, and forgiving of benevolent leadership and Shang-yan of authoritarian leadership can effectively stimulate employees' innovative behavior. Juan-Chiuan leadership is not conducive to employees' innovative behavior. Employees' high psychological safety and low uncertainty are important conditions for promoting employee innovation. In this study, the four dimensions of authoritarian-benevolent leadership and the psychological perceptions of employees are discussed in combination, and the paths of motivating employees to innovate actively are obtained. It is hoped that it can provide certain ideas for leaders to promote employee innovation.